Analisis penentu sektor basis dalam sistem bisnis rumput laut pada klaster Poleang Kabupaten Bombana - Sahara; Budiyanto; Yusuf, Sarini; Mansyur, Akhmad; Lawelle, Sjamsu Alam; Patiung, Seventry Meliana (Universitas Halu Oleo, 2024)
The base sector is a sector that has great potential in determining overall development in the region and becomes the backbone of the regional economy because it has a fairly high competitive advantage.This study aims to determine the determinants of the basis sub-sector in the seaweed business system in the Poleang Cluster, Bombana Regency. This research was conducted in April-May 2021, in Bombana District. The method used is purposive sampling technique with the consideration that Bombana Regency is an area that has abundant fishery potential and high economic value, especially seaweed. Data were obtained through interviews using questionnaires and analysis using the Location Quetient (LQ) analysis formula. The results of the Location Quetient analysis show that the highest base sector is in the Southeast Poleang Cluster with 12 bases, namely human resources, industry, electricity, clean water, markets, land transportation, sea transportation, ports, road conditions, communication conditions, used land and availability of seeds while the sector the lowest base is in the West Poleang Cluster with 3 bases namely retail, services and real taxes. The conclusion of this study is that the components that form seaweed clusters have formed naturally in Bombana.